Interplay of Things : Religion, Art, and Presence Together. - Pinn, Anthony B. (Duke University Press, 2021)
Drawing on literature along with the visual and performing arts, Anthony B. Pinn theorizes religion as a technology for interrogating human experiences understanding the ways in which things are always involved in processes of exchange and interplay.